Unveiling APOL1 haplotypes in a predominantly African-American cohort of kidney transplant patients: a novel classification using probe-independent quantitative real-time PCR - Dogan, Murat; Watkins, Christine; Ingram, Holly; Moore, Nicholas; Rucker, Grace M.; Gower, Elizabeth G.; Eason, James D.; Bhalla, Anshul; Talwar, Manish; Nezakatgoo, Nosratollah; Eymard, Corey; Helmick, Ryan; et al. (Frontiers in Medicine, 2024)
Introduction Apolipoprotein-L1 (APOL1) is a primate-specific protein component of high-density lipoprotein (HDL). Two variants of APOL1 (G1 and G2), provide resistance to parasitic infections in African Americans but are also implicated in kidney-related diseases and transplant outcomes in recipients. This study aims to identify these risk variants using a novel probe-independent quantitative real-time PCR method in a high African American recipient cohort. Additionally, it aims to develop a new stratification approach based on a haplotype-centric model. Methods Genomic DNA was extracted from recipient PBMCs using SDS lysis buffer and proteinase K. A quantitative PCR assay with modified forward primers and a common reverse primer enabled us to quantitatively identify single nucleotide polymorphisms (SNPs) and the 6-bp deletion. Additionally, we used Sanger sequencing to verify our QPCR findings. Results Our novel probe-independent qPCR effectively distinguished homozygous wild-type, heterozygous SNPs/deletions, and homozygous SNPs/deletions, with at least 4-fold differences. A high prevalence of APOL1 variants was observed (18% two-risk alleles, 34% one-risk allele) in our recipient cohort. Intriguingly, no significant impact of recipient APOL1 variants on transplant outcomes was observed up to 12-month of follow-ups. Ongoing research will encompass more time points and a larger patient cohort, allowing for a comprehensive evaluation of G1/G2 variant subgroups categorized by new haplotype scores, enriching our understanding. Conclusion Our cost-effective and rapid qPCR technique facilitates APOL1 genotyping within hours. Prospective and retrospective studies will enable comparisons with long-term allograft rejection, potentially predicting early/late-stage transplant outcomes based on haplotype evaluation in this diverse group of kidney transplant recipients.